2012
DOI: 10.1079/9781780641461.0000
|View full text |Cite
|
Sign up to set email alerts
|

Growth of farm animals

Abstract: Index x Contents Preface to First EditionAn understanding of the processes which change the size, shape and composition of farm animals is fundamental to all aspects of production which seeks to meet the dietary and other needs of human populations. This book attempts, within the limits of a basic undergraduate text, to give a comprehensive picture of how animals grow, change in shape and in composition, and to describe those factors which affect growth processes and which dictate the extent and direction of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 273 publications
(412 reference statements)
1
8
1
Order By: Relevance
“…Similarly, the higher relative weights of liver, kidney and small intestine in the Met− group can be explained by the suboptimal Met supply, which reduced muscle growth, but not the absolute weights of the internal organs. This is consistent with the view that the gastrointestinal tract and several internal organs in young animals have a high growth priority relative to muscle and fat tissue (Lawrence, Fowler, & Novakofski, 2012;Lilja, 1981).…”
Section: Growth Performance and Carcass Characteristicssupporting
confidence: 89%
“…Similarly, the higher relative weights of liver, kidney and small intestine in the Met− group can be explained by the suboptimal Met supply, which reduced muscle growth, but not the absolute weights of the internal organs. This is consistent with the view that the gastrointestinal tract and several internal organs in young animals have a high growth priority relative to muscle and fat tissue (Lawrence, Fowler, & Novakofski, 2012;Lilja, 1981).…”
Section: Growth Performance and Carcass Characteristicssupporting
confidence: 89%
“…The greater pH value for the LP group vs. MP in the present study was thus seemingly partially associated with the greater fat content in the former, although the difference between the two groups in fat content was not significant. Nonetheless, these results, as well as the greater protein content for the MP vs. LP group, are thought to be more of a mathematical significance rather than quality, in that the numerical differences between the two groups in the pH value and protein content were minimal within the normal ranges for the normal pork [14, 37, 38]. It needs to be noted, however, that the greater juiciness of cooked LM for the LP group vs. HP and MP groups is likely to have resulted from the greater WHC of fresh LM for the LP group, because WHC is one of the main factors enhancing the juiciness of cooked meat [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a compensatory growth usually occurs when the grower pigs fed a diet with a low lysine:- calorie ratio switch to a diet with a normal lysine:calorie ratio. The compensatory growth is frequently, but not always, concomitant with an increased feed intake and an increased fat deposition [13, 14], even though the fat deposition can be down-regulated during the compensatory growth for a compensatory lean gain which has priority over the energy retention [11, 1519].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the increase of SW results in a decreased production cost per unit weight of pork accompanied by slight increases in the dressing percentage and the yield percentage of the belly although growth rate and feed efficiency decrease following the increase of SW due to increased fat deposition [ 1 , 4 , 6 , 8 , 32 ]. It was therefore the rationale of the present study that if CW could be increased separately from the carcass grading system, the profitability would improve and the flavor of the meat might also improve [ 12 , 34 ], resulting in the improvement of pork quality, as was expected of the carcasses from the Hi and XHi groups of the present study mostly exceeding the 97-kg upper limit of Grade 1.…”
Section: Discussionmentioning
confidence: 94%
“…The SW seemingly influences meat quality primarily through its effects on fat metabolism. Intra-muscular fat (IMF), which increases marbling of fresh meat as well as the sensory attributes of cooked meat, including flavor, is known to increase with an increase in SW [ 11 , 12 ]. The IMF in the pork loin in the previous studies [ 4 7 ] indeed increased with the increase of SW, albeit to a limited extent, which did not influence sensory properties of cooked meat [ 8 ]; limited data regarding IMF for the ham precluded any assessment regarding the effect of SW on meat quality.…”
Section: Introductionmentioning
confidence: 99%